Neoadjuvant therapy strategies for advanced gastric cancer: Current innovations and future challenges - Zhi Zhu; Ying-Bo Gong; Hui-Mian Xu (Chronic Diseases and Translational Medicine, 2020)
Gastric cancer, which has a high incidence and poor prognosis, remains a therapeutic challenge. Recently, neoadjuvant therapy has attracted increasing attention due to high recurrence rate and low survival rate after resection in most patients with advanced stage. Clinical trials show that neoadjuvant approaches confer a significant survival advantage for resectable locally advanced gastric cancer. The specific advantages of chemoradiotherapy compared with chemotherapy have not been clarified; optimal regimens and cycles, particularly in the preoperative setting, should be studied further; and trials aimed at determining the role of targeted and immunological therapies should be conducted.